Review of research about parish nursing - King, Michalene A. (Online Brazilian Journal of Nursing, 2004)
Parish nursing is a unique type of community health nursing. Parish nurses do not perform hands-on nursing. Parish nursing care complements other health care delivery systems in the United States. Empirical literature about parish nursing is categorized into health needs assessment, parish nursing practice, and perceptions of parish nursing. Parish nursing can be seen as a means to reduce health care costs and improve the health of a community.